Pengaruh Pengetahuan Remaja Putri Dengan Kejadian Anemia di Kota Serang - Sella Victoria Amarilis Imbiri; Sarmi Satiri (Jurnal Ilmu Kesehatan dan Gizi, 2023)
The purpose of this study was to analyze the influence of knowledge of young women on the incidence of anemia in the city of Serang. The method used in this research is literature study by collecting data from a number of relevant literary references. The results of the study, from several literature reviews, found that young women had sufficient knowledge about anemia, and 77 (53.1%) young women had insufficient knowledge about anemia. As many as 92 percent of school-age girls in Serang City have anemia or anemia. This figure is the result of an anemia survey by the Serang City Health Office. The results of research on young women show the results of the level of knowledge of young women about anemia with the incidence of anemia. This is proven by the high level of anemia and the low level of knowledge of young women about anemia in the city of Serang